2002
DOI: 10.1023/a:1020998616007
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Endocrine cells are often found in human gastric carcinoma and may be recognized by the immunoreactivity of their chromogranin A, peptides and biogenic amines content. Anti-chromogranin A was used to investigate the morphology of endocrine cells using light and electron microscope immunohistochemical techniques. The hormone content of endocrine cells was examined in both tumour tissue and tumour-adjacent mucosa. It was found that the endocrine cells in tumour tissue were malignant, often had amphocrine differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Many studies showed that VIP was related with the gastric cancer [10, 18, 20]. We had showed that some gastric cancer cells in tumor tissues could secrete VIP [10].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that VIP was related with the gastric cancer [10, 18, 20]. We had showed that some gastric cancer cells in tumor tissues could secrete VIP [10].…”
Section: Discussionmentioning
confidence: 99%